1992
DOI: 10.1523/jneurosci.12-01-00290.1992
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by cAMP of a slowly activating potassium channel expressed in Xenopus oocytes

Abstract: When expressed in the Xenopus oocyte, the minK protein induces a slowly activating voltage-dependent potassium current (Isk). We studied the modulation of this current by altering intracellular cAMP levels and found that the amplitude of Isk is dramatically increased by treatments that raise cAMP levels and decreased by agents that lower cAMP levels. Preinjection of a protein inhibitor of the cAMP-dependent protein kinase blocked the effects of increased cAMP levels. There were no changes in the voltage depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…Thus, although the relationship to the disease remains to be clarified, we have shown that a channel involved in LQTS indeed is regulated by sympathetic stimulation. Interestingly, slowly activating delayed rectifier currents (I Ks ) recorded from oocytes injected with cRNA encoding minK also are stimulated by cAMP (17).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although the relationship to the disease remains to be clarified, we have shown that a channel involved in LQTS indeed is regulated by sympathetic stimulation. Interestingly, slowly activating delayed rectifier currents (I Ks ) recorded from oocytes injected with cRNA encoding minK also are stimulated by cAMP (17).…”
Section: Resultsmentioning
confidence: 99%
“…Our identification not only of KCNQ1 and KCNE1 as the molecular correlates of GC I Ks but also of 293B, L-735,821, and L-768,673 as specific antagonists of the current, will facilitate further investigation of its functional role. Additional experiments will be required to determine the basis for tissue-specific differences in I Ks modulation, particularly to address the discrepant effects of cAMP on GC I KS compared with recombinant KCNQ1/KCNE1 currents (Blumenthal and Kaczmarek, 1992) and native cardiac currents in guinea pig (Walsh et al, 1989) and pig (L. C. Freeman, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…MinK channels expressed in Xenopus oocytes show a similar slow activation as IK~ in guinea pig cardiac myocytes. In addition, the RNA encoding mink channels has been found in heart tissue of several species including guinea pig ( [4,6] minK channels and/Ks by second messengers has also been described [6,7,8,18]. Most recently, an identical sensitivity to novel class III antiarrhythmic compounds has been observed for Ir~s in guinea pig cardiac myocytes and minK channels expressed in Xenopus oocytes [19].…”
Section: Discussionmentioning
confidence: 99%